Flow structure and bubble dynamics in supercritical water fluidized bed and gas fluidized bed: A comparative study. (July 2015) - Lu, Youjun; Huang, Jikai; Zheng, Pengfei; Jing, Dengwei
Highlights: We compared the flow structure and bubble dynamics in the SCW and gas fluidized bed. A uniform flow structure was found in SCW fluidized bed after incipient fluidization. More but smaller bubbles were produced in SCW fluidized bed after uf exceeds umb . Solids' mixing in SCW fluidized bed is enhanced. No obvious trend is found in bubble amount/diameter versus bed height in SCW fluidized bed. Abstract: Supercritical water (SCW) fluidized bed is a new reactor concept for hydrogen production from biomass or coal gasification. In this paper, a comparative study on flow structure and bubble dynamics in a supercritical water fluidized bed and a gas fluidized bed was carried out using the discrete element method (DEM). The results show that supercritical water condition reduces the incipient fluidization velocity, changes regime transitions, i.e. a homogeneous fluidization was observed when the superficial velocity is in the range of the minimum fluidization velocity and minimum bubbling velocity even the solids behave as Geldart B powders in the gas fluidized bed. Bubbling fluidization in the supercritical water fluidized bed was formed after superficial velocity exceeds the minimum bubbling velocity, as in the gas fluidized bed. Bubble is one of the most important features in fluidized bed, which is also the emphasis in this paper. Bubble growth was effectively suppressed in the supercritical water fluidized bed, which resulted in a more uniform flow structure. By analyzing a large number of bubbles, bubble dynamic characteristics such as diameter distribution, frequency, rising path and so on, were obtained. It is found that bubble dynamic characteristics in the supercritical water fluidized bed differ a lot from that in the gas fluidized bed, and there is a better fluidization quality induced by the bubble dynamics in the supercritical water fluidized bed.